1997
DOI: 10.1021/bi971843e
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Alzheimer β-Amyloid Peptide(1−40) with Lipid Membranes

Abstract: The beta-amyloid peptide beta AP(1-40), a 40-amino acid residues peptide, is one of the major components of Alzheimer's amyloid deposits. beta AP(1-40) exhibits only a limited solubility in aqueous solution and undergoes a concentration-dependent, cooperative random coil reversible beta-structure transition for Cpep > 10 microM [Terzi, E., Hölzemann, G., and Seelig, J. (1995) J. Mol. Biol. 252, 633-642]. In the presence of acidic lipid, the equilibrium is shifted further toward beta-structured aggregates. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
351
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(391 citation statements)
references
References 70 publications
39
351
1
Order By: Relevance
“…Several laboratories have reported their CD work on A␤. Different experimental conditions may induce different A␤ conformations: (i) the ␣-helix in trifluoroethanol, SDS micelles, or induced by ganglioside-containing vesicles (34, 35, 46 -49), and also in our experiments when we used ethanol-water system to simulate the membrane condition, and the CD results indicate that the ␣-helix increases along with an increase of the ethanol content (data not shown), which coincides with the previous reports very well; (ii) essentially random-coil structures with ␤-turns in aqueous solution at low peptide concentrations; and (iii) ␤-structured aggregates in solution or in contact with lipid membranes (2,34). So far to our knowledge, systems containing cholesterol, which assuredly is the common component of membranes, are not employed yet in these published papers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several laboratories have reported their CD work on A␤. Different experimental conditions may induce different A␤ conformations: (i) the ␣-helix in trifluoroethanol, SDS micelles, or induced by ganglioside-containing vesicles (34, 35, 46 -49), and also in our experiments when we used ethanol-water system to simulate the membrane condition, and the CD results indicate that the ␣-helix increases along with an increase of the ethanol content (data not shown), which coincides with the previous reports very well; (ii) essentially random-coil structures with ␤-turns in aqueous solution at low peptide concentrations; and (iii) ␤-structured aggregates in solution or in contact with lipid membranes (2,34). So far to our knowledge, systems containing cholesterol, which assuredly is the common component of membranes, are not employed yet in these published papers.…”
Section: Discussionsupporting
confidence: 92%
“…By comparing the difference in the spectra among them in Fig. 4, we can find that the inaccessible cleavage sites are Gly 33 -Leu 34 and Gly 37 -Gly 38 . Both sites are located in the C-terminal region of A␤.…”
Section: Fig 3 Ms Spectrum Obtained For the Hydrolysis Fragments Ofmentioning
confidence: 99%
“…The protein molecules therefore are likely to intercalate into the cellular membrane. This conclusion is consistent with prior knowledge that the Aβ42 oligomer binds with high affinity with various membrane components, such as the outer envelope of polar headgroups, ganglioside clusters in raftlike structures, insulin receptors, α 5 β 1 integrin, and α7nAChR protein, to name a few (14,18,33).…”
Section: Disaggregated Aβ and Aβ Fibrils Reveal Much Less Impact On Nsupporting
confidence: 92%
“…To quantify contributions further, we separate (i) the binding of Aβ oligomers to various membrane components (such as the outer envelope of polar headgroups, ganglioside clusters in rafts, insulin receptors, α 5 β 1 integrin, and α7nAChR protein, to name a few) (14,18,33), and (ii) the treatment that alters membrane permeability by changing ion channels or making new pores, resulting in increased intracellular ion concentration. The former reduces fluidity and increases spring constant; the latter leads to greater osmotic pressure, which manifests into stiffer forcedeformation profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Both A␤ Protofibrils and HFIP-induced A␤ Aggregates Are Rich in ␤-Structure-Previous analyses of CD spectra for 39 -42-residue A␤ peptides prior to aggregation have concluded that the conformations are largely random coil in aqueous buffers (37,54) and predominantly ␣-helical in acidic (55) and neutral (56) pH solutions that contain Ն20% HFIP. Our spectra in Fig.…”
Section: Resultsmentioning
confidence: 99%